2012
DOI: 10.1167/iovs.12-10436
|View full text |Cite
|
Sign up to set email alerts
|

Acanthamoeba-Cytopathic Protein Induces Apoptosis and Proinflammatory Cytokines in Human Corneal Epithelial Cells by cPLAActivation

Abstract: PURPOSE. We have shown that Acanthamoeba interacts with a mannosylated protein on corneal epithelial cells and stimulates trophozoites to secrete a mannose-induced 133 kDa protease (MIP-133), which facilitates corneal invasion and induces apoptosis. The mechanism of MIP-133-induced apoptosis is unknown. The aim of this study was to determine if MIP-133 induces apoptosis and proinflammatory cytokines/chemokines in human corneal epithelial (HCE) cells via the cytosolic phospholipase A 2a (cPLA 2a ) pathway. CONC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 42 publications
(51 reference statements)
2
37
0
Order By: Relevance
“…However, macrophages have been demonstrated to persist at the site of infection (6,7), and therefore, they not only may be involved in initiating and maintaining an effective immune response, but also may have a role in tissue repair (8). To date, the majority of studies have examined the interaction between corneal epithelial cells (9)(10)(11) and Acanthamoeba, with comparatively few examining the interaction of these organisms with macrophages. Macrophages either can be long-lived cells patrolling the host's tissues (resident macrophages) or can originate from recruited bloodderived monocytes at the site of infection (elicited macrophages) (12).…”
mentioning
confidence: 99%
“…However, macrophages have been demonstrated to persist at the site of infection (6,7), and therefore, they not only may be involved in initiating and maintaining an effective immune response, but also may have a role in tissue repair (8). To date, the majority of studies have examined the interaction between corneal epithelial cells (9)(10)(11) and Acanthamoeba, with comparatively few examining the interaction of these organisms with macrophages. Macrophages either can be long-lived cells patrolling the host's tissues (resident macrophages) or can originate from recruited bloodderived monocytes at the site of infection (elicited macrophages) (12).…”
mentioning
confidence: 99%
“…Topical treatments (a combination of brolene, polyhexamethylene biguanide (PHMB), and chlorhexidine) are administered hourly for several weeks, but such therapies are not effective, and Acanthamoeba species can cause excruciating damage to the corneal epithelium and stroma, often resulting in practitioners' recommendations for corneal transplantation [5] . Study of AK pathogenesis raises the hope of solving difficulties in targeting therapeutic agents to treat AK; therefore, several studies have been orchestrated on the pathogenesis of AK [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] . More recently, we observed that Acanthamoeba trophozoites activate toll-like receptor 4 (TLR4) on human and Chinese hamster corneal epithelial cells in vitro and in vivo and stimulate cytokine secretion and progression of keratitis [24] .…”
Section: Research Articlementioning
confidence: 99%
“…Acanthamoeba castellanii (ATCC 30868), isolated from a human cornea, was obtained from the American Type Culture Collection (ATCC), Manassas, VA. Amoebae were grown as axenic cultures in peptone-yeast extract-glucose at 35°C with constant agitation on a shaker incubator at 125 rpm [21,34] . Human telomerase-immortalized corneal epithelial (HCE) cells, a gift from James Jester, PhD (University of California, Irvine), were cultured in keratinocyte medium (KBM-2 Bullet Kit; BioWhittaker, Lonza, Walkersville, MD) containing 10% fetal bovine serum (Hyclone Laboratories, Inc., Logan, UT), at 35°C with 5% CO2 [35] .…”
Section: Amoebae and Human Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…(a) Contact-dependent mechanism of the Acanthamoeba keratitis pathogenesis begins when Acanthamoeba trophozoites interact to the corneal surface by mannose binding protein (MBP) [11, 56] . This interaction releases the MIP-133 from A. castellanii trophozoites [15] , which interacts with membrane phospholipids on corneal epithelium and triggers arachidonic acid production, pro-inflammatory cytokines (IL-8, IL-6, IL-1β, IFNγ, and CXCL2), apoptosis, and polymorphonuclear neutrophils (PMNs) infiltration that leads to corneal lesion by the activation of cytosolic phospholipase A 2α (cPLA 2α ) pathway; cPLA 2α inhibitors (AACOCF3, CAY10650, and MAFP) therapeutically in vitro and in vivo mitigate inflammation and resolved the Acanthamoeba keratitis [60, 61] . (b) Contact-independent mechanism of the Acanthamoeba keratitis pathogenesis involves in the secretion of the Acanthamoeba plasminogen activator (aPA) which has been characterized a serine protease [8] .…”
Section: Acanthamoeba Keratitis and Pathogenesismentioning
confidence: 99%